Older Adults Show Less Flexible Spatial Cue Use When Navigating in a Virtual Reality Environment Compared With Younger Adults - Kimura, Kazushige (Neurosci Insights, 2019)
Daily life requires accurate navigation, and thus better understanding of aging on navigational abilities is critical. Importantly, the use of spatial properties by older and younger adults remains unclear. During this study, younger and older human adults were presented with a virtual environment in which they had to navigate a series of hallways. The hallways provided 2 general types of spatial information: geometric, which included distance and directional turns along a learned route, and featural, which included landmarks situated along the route. To investigate how participants used these different cue types, geometric and/or landmark information was manipulated during testing trials. Data from 40 younger (20 women) and 40 older (20 women) adults were analyzed. Our findings suggest that (1) both younger and older adults relied mostly on landmarks to find their way, and (2) younger adults were better able to adapt to spatial changes to the environment compared with older adults.